A Nomogram for Predicting Distant Metastasis Using Nodal-Related Features Among Patients With Nasopharyngeal Carcinoma - Xie, Chuanbo; Li, Haojiang; Yan, Yue; Liang, Shaobo; Li, Yanhong; Liu, Lizhi; Cui, Chunyan; Liu, Yuying (Frontiers in Oncology, 2020)
Distant metastasis is among the main reasons for treatment failure in nasopharyngeal carcinoma (NPC) patients. To identify patients with a high risk of distant metastasis is important to guide post-treatment surveillance, appropriate time treatments, and prolonging their long-term survival. In this study, we systematically examined the associations between a series of nodal related characteristics and distant metastasis free survival (DMFS) by detailed MRI reading and established a nomogram for DMFS in NPC patients.T-stage, age group, EBV level, central nodal necrosis, and nodal number were identified as independent risk factors for distant metastasis and were included into the final nomogram. The calibration plot showed a high agreement between the prediction by the nomogram and actual observations. Our established nomogram achieved A high C-index in predicting distant metastasis in both of the training cohort (0.737) and the validation cohort (0.718). This nomogram incorporated several readily available nodal features from the MRI images and it might be useful for guiding clinical decision and NPC patients’ post-treatment surveillance. It also provides cues for how to re-define N-stage. Additional research is needed to confirm our conclusions.